EFEKTIFITAS HIDROGEN PEROKSIDA DALAM MEMBUNUH BAKTERI AIR ULTRA SCALER PADA DENTAL UNIT DI RSIGM SULTAN AGUNG SEMARANG - Laily Maghfira Noor Ridarsyah; Djoko Priyanto; Grahita Aditya (Faculty of Dentistry, Universitas Islam Sultan Agung, 2015)
Background: Infection control is essential in dentristry. Many studies suggested an increase of bacteria in dental unit due to back flow from ultrasonic scaler. Previous study states that hydrogen peroxidein 3% concentration may reduce the number of bacteria's colony of ultrasonic scaler water in RSIGM Sultan Agung Semarang significantly. Purpose: The aim of this study was to determine the effectiveness of hydrogen peroxide to kill bacteria of ultrasonic scaler water on dental unit in RSIGM Sultan Agung Semarang. Method: The type of research used in the study is quasy experimental with pretest-posttest design. The sample used in this study is 15 dental units which were divided into 3 groups group I 2% hydrogen peroxide, group II 4.5% hydrogen peroxide, and group III 6 % hydrogen peroxide and than flow it on ultrasonic scaler water and check the bakteria before and after experiment. Result: Based on the results of Wilcoxon test the comparison before and after at the three groups obtained the results of significance is less than 0.05. It can be concluded thathydrogen peroxide effectively kills bacteria of ultrasonic scaler water on dental unit in RSIGM Sultan Agung Semarang. Conclusion: From the results it can be concluded that the percentage of hydrogen peroxide which can cause all organisms die without disturbing the patient's health is at 4.5% and 6% concentration.